(untitled) (International Integralize Scientific, 2026)
This article analyzes structural racism in Brazil based on its historical origins and its persistence in the present time. It is grounded on the understanding that racism does not consist merely of individual acts of discrimination, but constitutes a structural element of Brazilian social formation, articulating economic, political, and cultural dimensions. The study aims to examine the role of slavery, racialist theories, and the myth of racial democracy in the consolidation of social hierarchies, as well as to identify how these structures are reproduced in contemporary society. Methodologically, this is a qualitative study developed through a narrative literature review, based on academic databases and critical analysis of classical and contemporary works on the subject. Official statistical data were also used to contextualize current racial inequalities. The findings indicate that the abolition of slavery was not accompanied by structural inclusion policies, contributing to the maintenance of racialized inequalities in the labor market, income distribution, and access to rights. It is concluded that structural racism continues to operate as an organizing element of Brazilian society, requiring analyses that articulate history, economy, and coloniality for its understanding.